The study of the psychological health of first year students at the Univesity of Limpopo - Sakala, Ruvimbo (University of Limpopo, 2018)
Upon entering the university environment, first year students encounter what could be described as a “foreign culture”, and have to reconcile conflicting transitional spaces of their home and university identities. This adjustive demand can lead to some considerable levels of psychological distress. This study examined the level of psychological health in first year students. It also evaluated whether factors such as monetary background, residential area, race and the availability of bursaries affect students’ transition into “university life”. First year students (N = 300; male = 135; female = 165) completed the General Health Questionnaire-12 at the University of Limpopo. A substantial percentage (that is, 30.33%) of the participants was found to have or is prone to psychological health problems. This finding is consistent with the results of previous studies which have found that some students may be susceptible to mental health problems predating their entry into university. There was no significant difference between the levels of psychological health between males and females and bursary users and those that are funded by their parents or guardians. There was also no significant difference between those that live in the rural areas and those from the cities. However, the figures between those that are poor and rich were strikingly noteworthy.
Thesis (M. A. (Psychology)) -- University of Limpopo, 2018
Keywords: First year students; Psychological health; Stress; College students -- Psychology; Health -- Psychological aspects; Stress (Psychology); Distress (Psychology)